(untitled) (International Journal of Environmental Sciences, 2025)
The Quality of Work Life (QWL) is a generic phrase that is multifaceted and comprehensive in nature. The quality of work life covers a wide range of issues both financial and non-financial relating to work context, work contents and work relations. There was a growing realization that, in reality, behaviour depends upon the dynamic interaction between the individual and the organizational characteristics. the researchers have made an attempt to assess the QWL in the private banks in Villupuram District and give productive ideas to development Quality of Work Life in Banking Sectors. The objective of the study are asses the perception of Quality of Work Life and the level of job satisfaction of select private bank employees working in Villupuram District. For the purpose of the study, representative 150 employees have been selected from three private sector banks namely Karur Viysya Bank, ICICI Bank, City Union Bank by using convenience sampling techniques. The collected data was analyzed using percentage, mean, standard deviation and correlation co-efficient. It is found that the level of satisfaction is high that factors like Opportunities for Growth and Security, Opportunities for Growth and Security and Social Integration and Factors that ‘Social Relevance of Working Life is satisfied at low level in the Banks. level of job satisfaction are high factors like Co-Workers Relationship and Working Environment and Factors that ‘Health Care Benefit’, ‘Recognition’ and ‘recreational facilities’ are satisfied low level. There are significant and positively correlated between Job satisfaction and quality of work life.